Efficacy and Safety of Suprachoroidal Administration of Triamcinolone Acetonide in Patients of Refractory Diabetic Macular Edema - Hafiz Huzaifa Akhlaq, Fatima Akbar Shah, Muhammad Ahsen, Syed Ahmad Hassan, Khadija Zahid, Rafih Razzaq Wattoo, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To determine the efficacy and safety of suprachoroidal administration of triamcinolone acetonide in patients of refractory diabetic macular edema. Study setting: This study was conducted from September 2020 to April 2021 in the department of Ophthalmology FMU/Allied Hospital Faialabad. Study design was quasi experimental Materials and methods: sample size was 45, through non probability consecutive sampling. All 45 patients with refractory diabetic macular edema were enrolled and following parameters e.g Best corrected visual acuity (less than 20/40 on Snellen Visual acuity Chart),IOP < 21 mm of Hg, Central macular thickness >300 micrometers, were recorded as baseline at the start of study. Suprachoroidal triamcinolone acetonide injection 0.1 ml given to these 45 patients. Same parameters e.g Best Corrected visual acuity, Intraocular pressure, Central Macular Thickness were measured at each follow-up visit. First follow-up visit was conducted on next day then one week , one month and in third month. Results: In this study, mean of age was 50.71 ± 7.05 years. 23(51.1%) were males and 22(48.9%) were females. Pre-treatment Intra ocular pressure, best corrected visual acuity and macular thickness were 13.4± 1.9 mmHg ,0.72± 0.11 and 638.04 ± 133.9 micrometers respectively. After one-month Intra ocular pressure, Best corrected visual acuity and Central macular thickness were 13.71 ± 2.61 mmHg, 0.48± 0.11 and 314.11 ±53.8 micrometer and after three months 13.24±1.26mmHg, 0.46±0.12 and 306.9±49.52 micrometer respectively. Statistical significant difference was found for pre and post Best corrected visual acuity and Central macular thickness (p-value <0.0001).In two (4.4%) patients, intra ocular pressure was raised. Practical implication: This study was highlighted safety and efficacy of suprachoroidal injection of triamcinolone acetonide in cases of refractory diabetic macular edema Conclusion: Suprachoroidal Triamcinolone acetonide injection is proved to be safe and effective treatment modality for the patients of refractory diabetic macular edema as it decreases central macular thickness and improves best corrected visual acuity. Keywords: Diabetic macular edema, Suprachoroidal, Triamcinolone acetonide, Intra ocular pressure, Optical coherence tomography, visual acuity.